2016
DOI: 10.1111/1467-8268.12192
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Bribery: Theory and Evidence from Sub‐Saharan Africa

Abstract: The paper investigates the determinants of bribery in sub-Saharan Africa by using probit models and data from the World Bank's Enterprise Survey of 10,457 firms in 30 countries in sub-Saharan Africa from 2009 to 2013. By doing so we find that securing a government contract is the most significant motivation for bribery and that overall, the propensity to bribe depends on the size of the firm as well as the predictability of the regulatory environment. Our findings have similarities and differences compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 39 publications
(44 reference statements)
3
24
0
2
Order By: Relevance
“…In this light, the article adopts the governance indicators from Kaufmann, Kraay, and Mastruzzi 2010, consistent with a recent stream of literature on unbundling (Andrés and Asongu 2013;Andrés, Asongu, and Amavilah 2015;Gani 2011;Nwokora and Pelizzo 2017;Oluwatobi et al 2015;Nwokora 2016, 2018;Pelizzo et al 2016;yerrabati and Hawkes 2015) and bundling (Asongu 2016;Nwachukwu 2016c, 2017c) governance dynamics.…”
Section: Clarification Of Governancementioning
confidence: 85%
“…In this light, the article adopts the governance indicators from Kaufmann, Kraay, and Mastruzzi 2010, consistent with a recent stream of literature on unbundling (Andrés and Asongu 2013;Andrés, Asongu, and Amavilah 2015;Gani 2011;Nwokora and Pelizzo 2017;Oluwatobi et al 2015;Nwokora 2016, 2018;Pelizzo et al 2016;yerrabati and Hawkes 2015) and bundling (Asongu 2016;Nwachukwu 2016c, 2017c) governance dynamics.…”
Section: Clarification Of Governancementioning
confidence: 85%
“…FDI in Africa is hauled in by location-specific advantages that are driven by its natural resources (Arısoy, 2012;Aga, 2014). Zurawicki and Habib (2010) and Pelizzo et al (2016) observe that foreign firms face challenges caused by structural weaknesses in host economies, incomplete and unstable institutional frameworks, underdeveloped political and constitutional court systems, corruption and bureaucratic regulations. Majeed and Ahmad (2018) showed that both exports and FDI in Pakistan positively affect each other, although the effect of exports on FDI was not very significant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The governance mechanisms from Kaufmann, Kraay and Mastruzzi (2010) are increasingly being used in the governance literature. Some recent studies that have employed these six governance indicators include: Andrés et al (2015), Pelizzo, Araral, Pak and Xun (2016), Nwokora (2016, 2018), Nwokora and Pelizzo (2018), Oluwatobi, Efobi, Olurinola and Alege (2015), Ajide andRaheem (2016a, 2016b) and Asongu and Nwachukwu (2017b). According to the attendant literature: "The first concept is about the process by which those in authority are selected and replaced (Political Governance): voice and accountability and political stability.…”
Section: Datamentioning
confidence: 99%